TARIAN LEGO-LEGO PADA MASYARAKAT KAMPUNG TAKPALA KECAMATAN ALOR TENGAH UTARA KABUPATEN ALOR - Delita Rosalina Mauweni; Cindy Sintikhe Dollu, Bendelina Marta Malailo, Bendelina Alomau, Daud Bentro Maukallang, Halena Muna (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the Lego-Lego Dance in the Takpala Village Community, Alor Engah Utara District, Alor Regency. The method used in this research is qualitative research..., Ethnographic approach, and data collection techniques were carried out in two ways, namely field observations and interviews with Mr Anselmus Yetimau with the results of research showing that the Takpalah Village Community has a symbolic meaning in lego-lego dance movements, namely circular movements in the lego-lego circle contain the meaning of togetherness, unity, and interconnected harmony, The movement of embracing the shoulders or waist in the lego-lego circle contains meaning as a unifier in tying the rope of brotherhood between villagers without seeing each other's background status, men or women, ethnicity, nation, religion, economy and others but supporting each other, shoulder to shoulder and a high spirit of mutual cooperation, The movement of stomping feet in lego-lego dance has a symbolic meaning that describes strength, assertiveness, and high spirits.